Advances in Immunotherapy and the TGF-β Resistance Pathway in Metastatic Bladder Cancer - David J. Benjamin (MDPI AG, 2021)
Bladder cancer accounts for nearly 200,000 deaths worldwide yearly. Urothelial carcinoma (UC) accounts for nearly 90% of cases of bladder cancer. Cisplatin-based chemotherapy has remained the mainstay of treatment in the first-line setting for locally advanced or metastatic UC. More recently, the treatment paradigm in the second-line setting was drastically altered with the approval of several immune checkpoint inhibitors (ICIs). Given that only a small subset of patients respond to ICI, further studies have been undertaken to understand potential resistance mechanisms to ICI. One potential resistance mechanism that has been identified in the setting of metastatic UC is the TGF-β signaling pathway. Several pre-clinical and ongoing clinical trials in multiple advanced tumor types have evaluated several therapies that target the TGF-β pathway. In addition, there are ongoing and planned clinical trials combining TGF-β inhibition with ICI, which may provide a promising therapeutic approach for patients with advanced and metastatic UC.